COVID-19 and Related Vaccinations in Children: Pathogenic Aspects of Oral Lesions - Federica Di Spirito; Francesco D'Ambrosio; Maria Pia Di Palo; Francesco Giordano; Nicoletta Coppola; Maria Contaldo (MDPI AG, 2023)
Various clinical manifestations of SARS-CoV-2 infections and adverse reactions to COVID-19 vaccination have been described in children. The present narrative review aimed to collect and synthesize reported findings on oral lesions detected in SARS-CoV-2-positive subjects following COVID-19 EMA-authorized and WHO Emergency Use Listing-approved vaccine administration in the pediatric population to detail their clinical features and highlight possible pathogenic aspects of those lesions based on current evidence. Few and incomplete reports were retrieved from the literature, probably because most lesions belonged to a broad spectrum of systemic diseases and syndromes and were nonspecific or inaccurately described. The most common oral lesions in pediatric SARS-CoV-2-positive patients were erosive-ulcerative lesions and macules/petechiae, primarily erythematous. In the context of COVID-19 vaccination, oral adverse reactions were rare and typically presented as erosive-ulcerative lesions, with EM-like or unspecified patterns. Future studies should investigate oral lesions in SARS-CoV-2-positive subjects and after COVID-19 vaccination in the pediatric population, taking into account viral variants and newly developed vaccines. Deeper insight into oral lesions detectable in pediatric SARS-CoV-2-positive subjects and after COVID-19 vaccination may increase clinicians' ability to improve multidisciplinary pediatric oral and general care.